Acute and Subacute Toxicity of Aqueous Extract of Allium Cepa Peels in Wistar Albino Rats: Determination of acute and subacute toxicity in Wistar albino rats - Idowu Ojuade, Fatimoh; Oluwafunke Ayanniyi, Rashidat; Ayodeji Olumoh-Abdul, Hidayah; Rhoda Ayeni, Adedolapo; Wemimo Rasheed, Mumini (Iranian Journal of Pharmaceutical Sciences, 2021)
Allium cepa (A. cepa) is a medicinal plant widely used as spice in food and has been reported to have antiinflammatory, antiulcer, antidiabetic, antihypertensive, anticancer, and antioxidant properties amongst others. The peels from this vegetable also possess antioxidant, antiulcer, antidiabetic, antihypertensive activities to mention few. A. cepa peels is used by traditional healers to treat and or manage different ailments but little is known about the safety of A. cepa peels. This study evaluated the safety of aqueous extract of A. cepa peels (AEACP) in female Wistar albino rats. Oral acute toxicity was evaluated using Organization for Economic Cooperation and Development (OECD) guideline 423, three (3) oral doses of the extract (125, 250, and 500 mg/kg) were used and administered for 28 days for the subacute toxicity study. The effect of AEACP was evaluated on the: body weight, relative organ weight, hematological parameters, hepatic and renal parameters. The effect of AEACP was also evaluated on the histology of the kidney and liver. The median lethal dose (LD50) was estimated to be greater than 2000 mg/kg and administration of AEACP produced no significant (p˂0.05) differences in body weight, relative kidney weight, creatinine, and uric acid when compared with control group. There were significant (p˂0.05) reduction in relative liver weight, serum sodium, and serum chloride level in 500 mg/kg group and the percentage reduction in comparison with control was 15.24 ± 1.98, 42.45 ± 2.40, and 9. 65 ± 1.07 respectively. The PLT and ALT values in 125 mg/kg group were significantly (p˂0.05) lowered by 26.26 ± 2.96 and 39.46 ± 3.04% when compared with control. The WBC, uric acid, Albumin, and D. bilirubin values in 500 mg/kg group were significantly reduced (p˂0.05) compared with 125 mg/kg group with percentage reductions of 32.10 ± 2.31, 7.79 ± 1.03, 17.89 ± 2.34, and 27.37 ± 2.79 respectively. The urea level in groups treated with 125 and 250 mg/kg of AEACP was significantly lower than the control group and the percentage reduction were found to be 54.17 ± 2.10 and 37.15 ± 1.98 respectively. The histopathological examinations showed no traces of toxicity as the architecture of the liver and kidney were preserved. Acute and subacute use of Allium cepa peels produced no toxicity, its folkloric use is safe and should be encouraged.